'Children My Age Should Be Reading Books Like Journey to Jo'burg': Patterns of Anti-Racist Reading in Archived Reader Responses. Issue 3 (September 2022) - King, Helen
Abstract : Using archived reader responses to Beverley Naidoo's Journey to Jo'burg (1985), I employ the framework of Antiracist Pedagogy to explore how readers engage with the novel's indictment of racism in apartheid South Africa. Drawing on classroom responses from a variety of global contexts, I develop a context-orientated approach to reader response criticism that draws on theories of child agency developed by Karen Sánchez-Eppler (2005) and Robin Bernstein (2011). Using this approach, I identify four recurring patterns of engagement with the theme of racism: affect, identification, resistance, and critical literacy. Through my analysis, Naidoo's child readers emerge as partial subjects whose agency is not fixed but continuously negotiated in the play between text and context. These readers claim authority to speak about literature and their own experiences of racism, and conceive of radical, anti-racist literature as essential in their lives and those of their fellow children.